PERSEPSI POLITIK MASYARAKAT TERHADAP KEPEMIMPINAN BUPATI DAN WAKIL BUPATI TERPILIH DI KABUPATEN LAMANDAU PROVINSI KALIMANTAN TENGAH - Ivan Mura; Susilo Utomo (Journal of Politic and Government Studies, 2017)
Leadership includes the process of influence in setting organizational goals, motivate followers to achieve the objective behavior, influence to improve the group and its culture. Leadership has a close connection with motivation. It can be seen from the success of a leader in mobilizing others in achieving the goals set. One obvious example is the form of leadership success Regional Head managed to occupy his post for more than one period. Starting from the above problems, the authors try to determine how the public perception in the region that has a head area with a multi-period tenure.This paper aims to determine the perception Politics Society against district leader elected in the district of Central Kalimantan province Lamandau through Community Political Orientation. Political Perceptions is the political views of the subject to the object political politics. In the perception of national and state politics is a reasonable attitude possessed by every citizen as a sign of political culture creation..Kajian is done by non-parametric methods of quantitative research and written with descriptive analytical method. The author conducted a survey to determine the sample using Multistage Random Sampling method in the three District of the District Bulik, District and Sub-district Lamandau Delang by the number of respondents of the Hundred Double.The study results show the political culture of society in the study site has been running pretty well. It is caused by several factors including: 1) The level of education began to improve so that the level of political awareness also increased; 2) a high number of productive age; 3) the disclosure by the local government as a political object; 4) The policies offered by the government in accordance with the conditions of the community.Keywords: Perception of Political, Cultural Politics, Leadership.